Seals and sealing in the Ancient world : case studies from the Near East, Egypt, the Aegean, and South Asia - Ameri, Marta; Ameri, Marta; Costello, Sarah Kielt; Costello, Sarah Kielt; Jamison, Gregg; Jamison, Gregg; Scott, Sarah; Scott, Sarah (Cambridge University Press, 2018)
Studies of seals and sealing practices have traditionally investigated aspects of social, political, economic, and ideological systems in ancient societies throughout the Old World. Previously, scholarship has focused on description and documentation, chronology and dynastic histories, administrative function, iconography, and style. More recent studies have emphasized context, production and use, and increasingly, identity, gender, and the social lives of seals, their users, and the artisans who produced them. Using several methodological and theoretical perspectives, this volume presents up-to-date research on seals that is comparative in scope and focus. The cross-cultural and interdisciplinary approach advances our understanding of the significance of an important class of material culture of the ancient world. The volume will serve as an essential resource for scholars, students, and others interested in glyptic studies, seal production and use, and sealing practices in the Ancient Near East, Egypt, Ancient South Asia and the Aegean during the 4th-2nd Millennia BCE